2009
DOI: 10.4028/www.scientific.net/amr.79-82.553
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of Epoxy Resin Reinforced with Jeffamines-Grafted Carbon Nanotubes

Abstract: The increasing proliferation and application of advanced polymer composites requires higher and broader performance resin matrices. Poly(oxypropylene) with –NH2 end-groups has been widely used to toughen epoxy resins, but the strength of resin matrix may be reduced due to the addition of flexible segments in the crosslinking network. Carbon nanotubes (CNTs) have been paid more and more attention in recent years because of their superior thermal and mechanical properties. In this paper, CNTs grafted with Jeffam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…From the experimental results, it could be proven that epoxy resin nanocomposites reinforced with CMC/buckypapers have a positive influence on the thermal stability and lower degradation rate compared to pure polymer. This is a consequence of the high thermal conductivity of carbon nanotubes, which can efficiently enhance the heat transport from polymer to CNT to polymer [26]. In addition, dispersion is a key parameter deciding the thermal stability performance of polymer composites with particle fillers.…”
Section: Resultsmentioning
confidence: 99%
“…From the experimental results, it could be proven that epoxy resin nanocomposites reinforced with CMC/buckypapers have a positive influence on the thermal stability and lower degradation rate compared to pure polymer. This is a consequence of the high thermal conductivity of carbon nanotubes, which can efficiently enhance the heat transport from polymer to CNT to polymer [26]. In addition, dispersion is a key parameter deciding the thermal stability performance of polymer composites with particle fillers.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the addition of 1 wt% of MWCNTs in the polystyrene by solution evaporation procedure brought about 36-42 and almost 25 % enhancement in tensile modulus and tensile strength, in order (Suemori et al 2013). Whereas, the improvement in indentation resistance was recorded up to 3.5 times by supplementing 2 wt% SWCNTs in epoxy resin (Shi et al 2009;Huaming et al 2005). Some studies observed a major enhancement in modulus and hardness (1.8 times and 1.6 times) with the integration of 1 wt% MWCNTs in polyvinyl alcohol (Song et al 2013).…”
Section: Structural Applicationsmentioning
confidence: 99%
“…Oxidized CNTs well show an exceptional stability in other solvents including caprolactam, which is applied in the production of polyamide (Frohlich et al 2013). Study on carboxylation of CNTs has shown a considerable enhancement in interfacial bonding between CNTs and polymer matrices, which consecutively triggered stronger CNTs-polymer interaction, leading to improvement of Young's modulus and mechanical strength (Hashimi et al 2012;Shi et al 2009). Conversely, dramatic amounts of induced defects throughout functionalization hamper the intrinsic mobility of carriers along CNTs, which is not desirable in any case (Naeimi et al 2009;Liu et al 2011;Zhong et al 2011).…”
Section: Cnts: Carboxylation Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,8 Applicate flexible curing agents, such as Jeffamine, can be considered as one of the most effective methods to reduce the hardness of the epoxy network (Jeffamine is a low viscosity diamine with flexible and linear polyether backbone). 9 In addition, the usage of liquid rubbers is another successful method for reducing the hardness, improvement of the toughness, and decrease in the glass transition temperature (T g ), and modulus of the epoxy network (McGarry, first reported this method). 10 Among different types of liquid rubbers employed in this context, carboxyl terminated poly butadieneacrylonitrile (CTBN) has attracted considerable attention from the researchers.…”
Section: Introductionmentioning
confidence: 99%